1970
DOI: 10.2135/cropsci1970.0011183x001000010033x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Solar Radiation and Date of Planting on Yield of Sweet Sorghum

Abstract: Experiments were conducted to determine the influence of date of planting and solar radiatiou on yield of sweet sorghum stalks and sugar. Radiation received by the plants during the period between boot and early seed formation accounted for about 75% of the variation in yield. Maximum solar radiation in south Texas occurs during June, July, and August, consequently maximum yields were obtained from April, May, and June plantings.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

1973
1973
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…Devani & Blanco [17] reported a similar higher stalk yields in 29 th November sowings in field trials at Monte Redno Tucuman in C. V. Roma. Hipp et al [18] related these differences in Stem yield from different planting dates to difference in solar radiation received by plants. According to them cane yield was linearly related to radiation received during fruiting.…”
Section: Discussionmentioning
confidence: 99%
“…Devani & Blanco [17] reported a similar higher stalk yields in 29 th November sowings in field trials at Monte Redno Tucuman in C. V. Roma. Hipp et al [18] related these differences in Stem yield from different planting dates to difference in solar radiation received by plants. According to them cane yield was linearly related to radiation received during fruiting.…”
Section: Discussionmentioning
confidence: 99%
“…The proper sowing time exerts a marked effect on the growth and eventually on the yield of a crop. Sowing of the crop at right time ensures better plant growth and also inhibits weed growth" [2]. There are evidences that "optimum time of sowing is one of the several cultural manipulations and play vital role in boosting up the yield, particularly in Indian sub-continent where the optimum time of sowing varies to great extent due to varying agro-climatic conditions.…”
Section: Introductionmentioning
confidence: 99%
“…There are evidences that "optimum time of sowing is one of the several cultural manipulations and play vital role in boosting up the yield, particularly in Indian sub-continent where the optimum time of sowing varies to great extent due to varying agro-climatic conditions. The yield and quality of sweet sorghum has been reported to vary with different sowing dates" [2,3]. "Row spacing is also one of the important factor for crop establishment technique that affects the crop stand and other yield parameters in different crops.…”
Section: Introductionmentioning
confidence: 99%
“…Shading 21 days during the reproductive phase was more detri mental than shading 54 days during the vegetative phase or 63 days during the maturation phase. Hipp et al (13) observed that radiation received during the fruiting of sweet sorghum accounted for about 75% of the variation in yield.…”
mentioning
confidence: 99%